Productivity of a building-integrated roof top greenhouse in a Mediterranean climate. (November 2017) - Montero, J.I.; Baeza, E.; Heuvelink, E.; Rieradevall, J.; Muñoz, P.; Ercilla, M.; Stanghellini, C.
Abstract: Urban Agriculture (UA) is an emerging field of agricultural production aimed to improve food security and the resilience of cities and to improve the environmental, social, and economic sustainability of urban areas. One of the options of UA are roof top greenhouses (RTGs), which are greenhouses built on the roof of a building, typically fitted with soilless culture systems. Further benefits can be achieved if the greenhouse and building are integrated, so that they exchange and optimise energy, water and CO2 flows. Integration is possible if the RTG and the building can exchange air and can collect rain water or use properly treated grey water for irrigation. Such type of integrated RTG is referred to as i-RTG. Both the environmental profile and the social value of i-RTGs have been studied, but information on their productivity is rather scarce. As the economic viability of i-RTGs is given by the value of all services provided, including the yield, the productivity of such systems needs to be maximised. This study attempts this, through the analysis (and discussion) of an i-RTG built in a Mediterranean climate (Barcelona area, Spain), producing beef type tomatoes ("Coeur de boeuf" cultivar). The experimental study showed that the i-RTG had poor light transmission. As a consequence, yield was low and the radiation use efficiency (RUE), referred to the outside radiation, was lower than in standard production (unheated greenhouses) in the same region. Nevertheless, RUE referred to the radiation above crop canopy, was similar in the i-RTG and standard greenhouses. Compared to conventional greenhouses in the area, which are generally unheated, a strong asset of the i-RTG was its improved (night-time) temperature regime, thanks to the thermal connection to the building. This advantage translates into energy savings referred to greenhouses on the ground, in case such greenhouses were heated. In order to discuss possible improvements, we adapted an existing greenhouse tomato production model to simulate this particular type of system. After validation, we quantify and discuss the yield rise that could be achieved by improving transparency of the RTG and by increasing CO2 concentration through daytime connection to the building. We show that there is potential to more than double the yield in comparison with the measured crop yield in the i-RTG. Last but not least, we discuss the option of switching to a cropping pattern more adequate for this growing system, that is: to extend the cropping cycle during the winter months, which is not possible in unheated greenhouses in the area. To our knowledge, this work is the very first attempt to evaluate productivity of roof top greenhouses in mild winter regions and quantify options for improving their agronomic performance. Highlights: It is a study of a typology of Urban Agriculture (UA) about which information is rather scarce. This is the first attempt to evaluate RTGs in mild winter regions, and quantify options to improve their productivity. The climate of the RTG in terms of solar radiation, temperature, humidity and CO2 concentration is described. The integration of the RTG and building in terms of energy flow, water flow and air (CO2 flow) is discussed.